Training of Lemuru Fish Nuggets Processing for Stunting Children’s Mothers In Pantai Labu Sub-District Deli Serdang Regency - Lestrina, Dini; Tarigan, Novriani; Martony, Oslida (Journal of Saintech Transfer, 2020)
Failure of stunting in children will produce human resources that cannot compete in the era of globalization, affect work productivity, increase the risk of obesity, and lead to metabolic syndrome. Indonesia has a high incidence of stunting among children under five and school children, including North Sumatra with a prevalence of 42.3%, ranked fourth in the province with a high stunting prevalence. The prevalence of stunting in children aged 5-12 years increases every year. During the growth of very high bone mineralization, low intake of protein, calcium, and zinc influences linear growth. Aged 5-12 years is an opportunity to catch up and improve height. In terms of overcoming the lack of protein, calcium, and zinc intake as well as spurring the growth of schoolchildren, it can be done by giving Lemuru fish nuggets. Fish nugget processing is a simple processing method and has a long shelf life, with storage life in the freezer was 2 weeks. From the results of conseling and training conducted an initial and final knowledge assessment, it is known that initial knowledge is still lacking with an average value of 64.69 after the activity has increased to 83.95. Participants better understand the benefits of local food such as lemuru fish to cope with the stunting situation experienced by their child.